Factors affecting mothers’ awareness of digital gaming addiction - Pazarcıkcı, Fahriye; Efe, Emine (Journal of Dependence, 2022)
Objective: This study was conducted to determine the factors affecting mothers’ awareness of digital game addiction. Methods: The study is a cross-sectional study. The sample of study consisted of 287 mothers with children aged 1-17. The research data is collected through an online questionnaire using the Personal Information Form and the Awareness of Digital Game Addiction Scale (ADGAS). Results: The mean age of the mothers is 31.21±6.46. 36.9% of mothers have one child, 43.9% of them have been using a smart phone/tablet PC (personal computer) for 6-10 years. In the study, it is found that mothers have high awareness of digital game addiction. The internal awareness of digital game addiction of mothers who have been using a smart phone/tablet PC for 11 or more years was found to be statistically significantly higher than the other mothers. In addition, the external awareness of digital game addiction and the total score of ADGAS of mothers with one child are statistically significantly higher than mothers with two or more children. Conclusion: The mothers’ awareness of digital game addiction was high, and the duration of smartphone/tablet PC use and the number of children were affected by their awareness of digital game addiction. It is recommended to plan studies to increase the knowledge of mothers on digital game addiction and to support digital environment and digital parenting roles.